Bone regeneration is associated with the concentration of tumour necrosis factor-α induced by sericin released from a silk mat. Issue 1 (December 2017) - Jo, You-Young; Kweon, HaeYong; Kim, Dae-Won; Baek, Kyunghwa; Kim, Min-Keun; Kim, Seong-Gon; Chae, Weon-Sik; Choi, Je-Yong; Rotaru, Horatiu
Abstract To understand the osteogenic effect of the middle layer of the silk cocoon, sericin was examined for its cellular effects associated with tumor necrosis factor-α (TNF-α) signaling in this study. The fragmented sericin proteins in the silk mat were evaluated for the TNF-α expression level in murine macrophages. The concentration of protein released from silk mats was higher in the outermost and the innermost layers than in the middle layers, and the protein released from the silk mat was identified as sericin. The level of TNF-α in murine macrophages was dependent on the applied concentration of sericin, and the expression of genes associated with osteogenesis in osteoblast-like cells was dependent on the applied concentration of TNF-α. In animal experiments, silk mats from the middle layers led to a higher regenerated bone volume than silk mats from the innermost layer or the outermost layer. If TNF-α protein was incorporated into the silk mats from the middle layers, bone regeneration was suppressed compared with unloaded silk mats from the middle layers. Accordingly, silk mats from the silk cocoon can be considered to be a fragmented sericin-secreting carrier, and the level of sericin secretion is associated with TNF-α induction and bone regeneration.